Standarization of an ELISA test to detect IgE antibodies in patients with cystic echinococcosis and its use in diagnosis and follow-up of patients treated with albendazol: preliminary report - Castro S., Gina (2012)
The objective of this study was to standardize and validate the real-time RT-PCR technique for diagnosis of Infectious Pancreatic Necrosis virus (IPNV) in rainbow trout (Oncorhynchus mykiss) from Central Sierra of Peru. Samples of kidney and spleen (n=61) of rainbow trout with apparent clinical signs of IPN and from rainbow trout apparently healthy (n=60) were collected from two fish farms located in the central sierra. Before standardization of the real-time RT-PCR technique, the kidney and spleen samples of 121 rainbow trout were tested for antigen of IPNV by indirect immunofluorescent (IIF) test. In addition, kidney and spleen samples of 10 rainbow trout negative to IPNV by IIF were inoculated with a serial dilution of IPNV strain (from initial concentration of 103 PFU/ml). The RNA extraction of the 121 samples and of the 10 samples inoculated with IPNV strain, the cDNA and the real-time RT-PCR were carried out by commercial kits. The WB1 and WB2 primers were used to amplify a segment that codifies the protein VP2 of the Aquabirnavirus. A strain of IPNV as a positive control and Rotavirus A strain, Gumboro disease virus, bovine viral diarrhea virus, and parainfluenza-3 were used as negative controls. The 121 kidney and spleen samples were negative to IPNV by IIF test. The results of real time RT-PCR technique were evaluated considering the cycle threshold values of 31.7 and temperature melting of 80.4 °C of the amplicons. The real time RT-PCR technique was able to detect a concentration of 102 PFU/ml of IPNV in the kidney and spleen samples inoculated and the 121 of kidney and spleen samples were negative to IPNV. This technique had 100% of sensibility and specificity for detection of IPNV.